2022
DOI: 10.1111/nuf.12732
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nursing students' intention to attend face‐to‐face classes on school reopening: A theory of planned behavior application

Abstract: Background:The COVID-19 pandemic has resulted in school closures and the reopening of schools is considered to be a possible approach to start reversing learning deficits. However, the literature is scarce on the determinants of intention to attend face-to-face classes among nursing students.Method: This cross-sectional study examined students' intention to attend limited face-to-face classes on school reopening, and its association among the core constructs of the Theory of Planned Behavior. Undergraduate nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…Anecdotal evidence from our students revealed that students did not want to return to the classroom initially due to the fear of getting infected and subsequently due to costs. This contrasts with the findings in a study of nursing students in the Philippines 14 . As cases reduced, our students wanted the sessions to remain online and recorded.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Anecdotal evidence from our students revealed that students did not want to return to the classroom initially due to the fear of getting infected and subsequently due to costs. This contrasts with the findings in a study of nursing students in the Philippines 14 . As cases reduced, our students wanted the sessions to remain online and recorded.…”
Section: Discussioncontrasting
confidence: 64%
“…This contrasts with the findings in a study of nursing students in the Philippines. 14 As cases reduced, our students wanted the sessions to remain online and recorded.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of other factors such as internet literacy, moral obligation, and past behavior were also found to predict the plagiarism intention of nursing students in this study. Studies conducted locally and abroad (Al Maskari et al, 2022 ; Ditching et al, 2020 ; Oducado et al, 2022 ; Secginli et al, 2021 ; Zhong et al, 2022 ) have similarly found the TPB a helpful framework in successfully explaining the behavioral intention of nursing students.…”
Section: Discussionmentioning
confidence: 97%
“…Based on their background in nursing, nursing students could understand the necessity, effectiveness, and safety of the COVID-19 vaccine, as evidenced by their willingness to get the vaccination (Jiang et al, 2021). Furthermore, the study of Oducado et al (2022) disclosed that nursing students highly intend to attend face-to-face classes. During data collection, only vaccinated students of higher education institutions were allowed to join limited face-to-face classes.…”
Section: Discussionmentioning
confidence: 99%